Nano-Catalysts in Ozone-Based Advanced Oxidation Processes for Wastewater Treatment - Dang, Thi Thom; Do, Van Manh; Trinh, Van Tuyen (Current pollution reports, 2020)
Purpose of Review Pollution is now being varied with huge contaminants in wastewater especially with kind of recalcitrants that are emerging pollutants needed new advanced resolutions to mineralize them completely. Thus, the investigation of technology and technique processes is very important for research and development. Moreover, these manual, research, and application of the advanced oxidation processes especially using ozone for water and wastewater are concentrated and appreciated in over the world. Recently, nanoparticles have researched into subjects to enhance new, advanced technology for many domains such as environment, biology, agriculture, and medicine. Hence, the purpose of this review is to summarize the important role of nano-particulars as nano-catalysts in ozone-based advanced oxidation processes for wastewater treatment and evaluate how to contribute into ozone-based advance oxidation processes by nano-catalysts for wastewater treatment. Recent Findings The advanced oxidation processes (AOPs) for wastewater treatment nowadays are being appreciated in the twenty-first century when economy development day by day is concentrated extremely in industry, agriculture, and pharmacy leading to various pollutants in the environment. According to these developments, amount of various contaminants is discharged in wastewater; thus, investigation of advance technology based on nano-catalysts combining the ozonation will meet the demands for wastewater treatment. Summary This review found potentials and prospects of nano-catalysts applied in the catalytic ozonation process for wastewater treatment. Efficiency of some well-known nano-catalysts with analytical properties for catalytic ozonation is also evaluated. Mechanisms of this process are identified to easily approach the catalytic ozonation using nano-materials for wastewater treatment in the future.